A comprehensive review on the material performance affected by gaseous alternative fuels in internal combustion engines. (September 2022) - Liu, Zhongzhi; Guo, Zhiwei; Rao, Xiang; Xu, Yicong; Sheng, Chenxing; Yuan, Chengqing
Highlights: Corrosion, thermal damage, and wear issues in gaseous-fueled engines were summarized. Compatibility of engine materials with hydrogen, ammonia, and natural gas was evaluated. Tribology was introduced for improving the durability of crucial engine components. Hydrogen appears to be a promising but challenging fuel for engines. Abstract: Stringent requirements in emissions and the depletion of conventional fossil fuels drive the development of Gaseous Alternative Fuels (GAF). As a commonly used power source, compatibility issues of the internal combustion engines under the harsh conditions created by the fuels become a technical barrier to improving the safety, reliability, and power performance of real-world engines' applications. This paper systematically reviewed the material performance affected by GAF from the perspective of crucial engine components. Issues related to the compatibility of crucial components with GAF were firstly summarized in corrosion, thermal damage, and wear. Experimental study progresses concerning these compatibility issues and the assessment criteria for the material performances were discussed. Feasible critical technologies for improving material performances were discussed from tribology. Finally, this review briefly discussed the characteristics and plausible future trends for these compatibility issues. This study provides technical assistance for the safe application of GAF on internal combustion engines.